Application of Fiber-reinforced Concrete in Tram Track Foundation. (2017) - Garbaruk, V.V.; Dudkin, E.P.; Ivliev, V.A.
Abstract: The use of polymer fiber-reinforced concrete is one of the most promising trends in tram track development. It was first successfully used as tram track foundation in 2010-2011. The analysis of such structures has shown a number of their advantages: reduced construction time, economic benefits in terms of reducing cost and labour, and construction technology simplification. Mathematical modelling of structure strength characteristics and field testing specifying the model parameters are required for the subsequent use of fiber-reinforced concrete as tram track foundation.